Investigating factors affecting co2 emissions in Malaysian road transport sector - Mustapa S.I.; Bekhet H.A. (Econjournals, 2023)
Today the unprecedented increase in CO2 emissions has become an important global issue because of the intensification in demand from the transport sector due to an upward surge in urbanization and rapid economic growth. The demand for transport services is expected to rise further, causing the CO2 emissions level to increase as well. In Malaysia, the transportation sector accounts for 28% of total CO2 emissions, of which 85% comes from road transport. This has led to strong interest in how the CO2 emissions in this sector can be reduced effectively. This study aimed to investigate factors that influence the CO2 emissions. A multiple regression model was used based on fuel-based technology data for 1990-2013. Many factors influencing CO2 emissions, i.e., fuel consumption, fuel efficiency (FE), fuel price (FP) and distance travel (DT), were examined for the road transport sector in Malaysia. The results demonstrated that FE, FP and DT were the main factors influencing the CO2 emissions growth. Some policy implications from the empirical results were proposed for CO2 emissions reduction. 2015, Econjournals. All rights reserved.